Application of chitosan and its derivatives in Cu(II) ion removal from water used in textile wet processing. Issue 14 (September 2014) - Chattopadhyay, DP; Inamdar, MS
The applicability of chitosan, trimethyl chitosan chloride and nano-chitosan for removal of Cu(II) ions from water used in textile wet processing was studied. The liquor before and after treatment was analyzed iodometrically to find the presence of Cu(II) ions, and Fourier transform infrared spectroscopy was employed for the characterization of the chitosan–Cu(II) complex. The study included the effect of molecular weight of chitosan, particle size of chitosan and the degree of quaternization of trimethyl chitosan chloride, pH of the medium, etc., on the sorption of Cu(II) ions. The influence of the molecular weight of chitosan was found to be an important criterion on the rate of sorption of Cu(II) ions. Reduction in the particle size of chitosan enhanced both the rate and amount of scavenging of metal ions.